Evaluación del sistema de agua potable de la parroquia Nanegal. - Changoluisa Moreno, Alexandra Elizabeth (2015)
The project contains a description detailed of the studies and redesign realized, to improve the system of drinkable water, of the parroquia Nanegal, situated in the cantón Quito. Province of Pichincha. It realized a census to the population beneficiary, the cadastral lifting of the existent structures, the evaluation hydraulic of the elements, and the determination of the discharges of design to a life useful of 30 years, with the end to identify the lacking of the system. The line of driving and the network of distribution fulfill with the norm of the Empresa Pública Metropolitana de Agua Potable y Saneamiento of Quito; but the catchments and the cameras break pressure find in bad conditions, and the tanks of existent storage, are not sufficient to keep the current and future demand. It proposes like alternatives of solution the implementation of a tank of reservation of 100 m3, with a hut of chlorination of 500 lt, the extension of the network of distribution in 316.66m, the improvement of the hydraulics and esthetics conditions, of the catchments and cameras breaks pressure, to end to guarantee the efficiency of the system for his good operation.